Histopathology and prognosis of malignant colorectal polyps treated by endoscopic polypectomy. Issue 5 (May 1984) - Morson, B C; Whiteway, J E; Jones, E A; Macrae, F A; Williams, C B
Abstract : The histopathological features and results of treatment of malignant polyps removed by endoscopic polypectomy from 60 patients are presented. The patients were followed for a minimum of five years. Forty six patients were treated by polypectomy alone as local excision was judged complete and the invasive carcinoma was well or moderately well differentiated. Thirty seven of these patients are alive and well after five years and the remaining nine have died of other causes up to four years later: there was no evidence of recurrence in any of these cases. Fourteen patients underwent a subsequent major surgical resection and residual tumour was found at the site of polypectomy in two cases but regional lymph nodes were not involved. Only one patient from this group with a high grade tumour developed metastases although the operative specimen was free of tumour. Malignant polyps can be successfully treated by polypectomy alone provided both the laboratory techniques of examination and the histopathological criteria are strictly applied.